The Effect of Web-Based Language Learning Activities on Reading Comprehension in the EFL Classroom - Sulistianingsih, Endang; Taufiqulloh, Taufiqulloh; Wardhani, Sri; Jamaludin, Sanday (Jurnal Bahasa Inggris, 2021)
This article presents the findings of a Web-Based Language Learning (WBLL) design which is established as a website as supplementary materials to offer instruction for English as a foreign language (EFL) and investigated it over undergraduates in the EFL context. The website contains task-based web activities which insist students use the Internet to achieve specific goals. This article employed a mixed-method where both qualitative and quantitative were used to answer the research questions. The results indicated that those who participated in the WBLL classroom and used the website had positive impressions of WBLL, demonstrated good comprehension, and expressed a desire to use more web activities both in and out of class.